Calculus

6x-3y=4 find dy/dx using differentiating implicity

  1. 👍 0
  2. 👎 0
  3. 👁 171
asked by Ivan
  1. 6 dx -3 dy = 0
    dy = 2 dx
    dy/dx = 3

    1. 👍 0
    2. 👎 0
    posted by Damon

Respond to this Question

First Name

Your Response

Similar Questions

  1. calculus3

    x^2/3+y^2/3=5 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  2. calculus2

    x^2+2y^2-11=0 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  3. calculus1

    x^5-5y=6-x find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  4. calculus4

    2y^3-y=7-x^4 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  5. calculus5

    (y^2+2)^3=x^4y+e^2 find dy/dx using differentiating implicity

    asked by Ivan on November 28, 2010
  6. Calculus

    Find the derivative of the function y, below. It may be to your advantage to simplify before differentiating. y = 8x(ln(x)+ln(2))-4x+pi

    asked by Nate on October 14, 2013
  7. Math

    Find the general antiderivative of f (x) and check your answer by differentiating. f(x) = x^5 + 9 Need Help.

    asked by Jason on July 1, 2010
  8. Calculus

    Find the derivative of f. you may simplify before differentiating f(x)= x2-7x+12/x4-8x3+13x2+30x-72

    asked by HELP!! on March 9, 2011
  9. Maths

    How would you solve this in order to find t? 0.2t(t-5.1)(t-9.1)=2.4+0.75t I tried differentiating it, but I wasn't getting the answer I was supposed to

    asked by alicia on October 9, 2015
  10. Calculus

    Integrate x dx/(1-x). I have proceeded thus- Int xdx/(1-x)=int -(x-1+1)/(x-1) =-Int[1+ 1/(x-1)]dx =-Int dx-Int dx/(x-1) =-x-log(x-1). On differentiating, we get original expression- d/dx[-x-log(x-1)]=-1-1/(x-1)=-x/(x-1)=x/(1-x).

    asked by MS on January 8, 2014

More Similar Questions